Demographic viability and ecology of the wild white-naped mangabey Cercocebus lunulatus (Temminck, 1853) in Comoé National Park, north-eastern Côte d’Ivoire: population size, group structure and food availability - Karim Ouattara; Tchinyo Coulibaly; Amara Ouattara; Inza Kone (Primates, 2026)

Low genetic diversity in Colobus vellerosus populations in Kikélé Sacred and Okuta Kobunan Forests, Benin - F. Darius Accrombessi; S. S. Mireille Toyi; Inza Kone; David J. Zinner; David Djimenou; Chabi A. M. S. Djagoun; Christian Roos; Dietmar Zinner (Primates, 2026)

Towards Trustworthy Artificial Intelligence for Marine Research, Fisheries and Environmental Management - Jose A. Fernandes‐Salvador; Angel Borja; Asier Anabitarte; Igor Granado; Xabier Lekunberri; Yolanda Sagarminaga; Oriol Canals; Anders Lanzen; Mihailo Azhar; Jonne Kotta; Henn Ojaveer; Anna Spinosa; et al. (Fish and Fisheries, 2026)
Artificial Intelligence (AI) is advancing at an unprecedented pace, offering transformative opportunities for marine research, fisheries management, environmental governance and policy development. Particularly in the context of the interconnected data needs of ecosystem management and biodiversity conservation, these technologies can enhance data acquisition, processing and decision support, enabling more integrated approaches to ecosystem management and biodiversity conservation. Yet their adoption in these domains remains limited by the absence of coherent frameworks that ensure transparency, validation and ethical alignment with ecological and socio‐economic sustainability goals. This work proposes a comprehensive framework built on three critical pillars for trustworthy AI: socio‐economic and legal viability, data governance and technical and scientific robustness. On the one hand it aims to be a guideline for developer teams. On the other hand, it aims to be a guideline for final users (e.g., industry and managers) for designing the requirements and evaluating such systems. The first pillar underscores the need for AI systems that are cost‐effective, scalable, environmentally sustainable and legally supported, balancing short‐term costs with long‐term social and ecological benefits. The second stresses adherence to fair, reliable and ethical access to digital resources, recognising that without strong governance data and algorithms risk becoming fragmented or misused. The third pillar addresses the necessity of rigorous validation across entire AI pipelines, including preprocessing, model evaluation and benchmarking against alternative ground truths, to ensure reliability in real‐world applications. Together, these pillars provide a blueprint for developing ethical, reliable and policy‐relevant AI systems that can strengthen trust, improve sustainability and guide decision‐making across marine science, fisheries, environmental management and European legislation.

Effectiveness of treatments for propranolol toxicity: a systematic review of current approaches and evidence - Yafei Hu; Khizra Mujahid; Awais Ahsan; Anika Fatima; Inza; Maham Maqsood Ahmed; Maham Anoosh Butt; Sadia Younas; Muhammad Arif Aslam; Hafiz Muhammad Ahmad Javaid (European Journal of Clinical Pharmacology, 2026)

Moderate water stress improve resistance to anthracnose rot in Arbequina olive fruits - Paula Conde-Innamorato; Georgina Paula García-Inza; Jeremías Mansilla; Gabriela Speroni; Eduardo Abreo; Carolina Leoni; Inés Ponce de León; Omar Borsani (European Journal of Plant Pathology, 2025)

An innovative optimized protocol for high-quality genomic DNA extraction from recalcitrant Shea tree (Vitellaria paradoxa, C.F. Gaertn) plant and its suitability for downstream applications - Affi Jean Paul Attikora; Souleymane Silué; Saraka Didier Martial Yao; Caroline De Clerck; Leonard Shumbe; Nafan Diarrassouba; Inza Jésus Fofana; Taofic Alabi; Ludivine Lassois (Molecular Biology Reports, 2024)

Determinants of bushmeat supply sources in rural areas of Côte d’Ivoire - Joseph A.K. Kouassi; Yves A. Kablan; Mona E. Bachmann; Sylvain R.T. Lemoine; Martin R. Nielsen; Inza Koné (Journal for Nature Conservation, 2023)

Impacts of climate change on regional cattle trade in the central corridor of Africa - Ariane Amin; Abdrahmane Wane; Inza Kone; Michel Krah; Ange N’Goran (Regional Environmental Change, 2023)

On the inner dynamics between Fossil fuels and the carbon market: a combination of seasonal-trend decomposition and multifractal cross-correlation analysis - Faheem Aslam; Ijaz Ali; Fahd Amjad; Haider Ali; Inza Irfan (Environmental Science and Pollution Research, 2022)

Energetic management in wild chimpanzees (Pan troglodytes verus) in Taï National Park, Côte d’Ivoire - Prince D. Valé; Jean-Claude K. Béné; Antoine K. N’Guessan; Catherine Crockford; Tobias Deschner; Inza Koné; Cédric Girard-Buttoz; Roman M. Wittig (Behavioral Ecology and Sociobiology, 2021)
Socioecological theories predict that, in mammals, feeding and mating competitions affect male and female energetic conditions differently but energetic studies investigating both sexes simultaneously are rare. We investigated the effect of socioecological factors on the energetic conditions of male and female western chimpanzees, a long-lived species with high degrees of male-male competition. We used behavioural data collected on one chimpanzee community in the Taï National Park over 12 months, phenological data and urinary c-peptide (UCP) measures, a marker of energy balance. We found a positive effect of food availability on UCP levels in both sexes. Dominance rank also affected chimpanzee UCP levels. High-ranking females had higher UCP levels than low-ranking ones but only in periods when no oestrus females were present in the community. In contrast, high-ranking males had higher UCP levels than low-ranking males in the presence of oestrus females but lower UCP levels in their absence. Our results suggest that oestrus female presence lessened the competitive advantages of high-ranking females in feeding competition and that low-ranking males bore higher energetic costs related to mating competition than high-ranking ones. Yet caution should apply in interpreting these results since the statistical model was only close to significance. High-ranking male and female chimpanzees spent significantly less energy. Furthermore, all chimpanzees significantly spent less time feeding and spent more energy when food availability was high. Finally, our behavioural measure of energy intake and expenditure did not correlate with UCP levels highlighting the value of non-invasive hormonal markers for field studies. Significance statement General socioecological theories hypothesize that the social grouping dynamic and energetics of females are highly influenced by food competition, whereas in males, competition for sexual partners is more influential for these factors. Recent studies in the non-invasive physiological assessment of energy balance in primates have begun to test the implied relationship between chimpanzee socioecology and individual energetic condition, with inconsistent results. However, only a few studies have investigated this relationship concurrently for both sexes. Here, using non-invasive measures of energy balance in wild western chimpanzees, we found that the energetics of both males and females are related to ecological factors, such as food availability. However, female energy balance appears also to be related to increased male mating competition, as this can result in increased aggression directed from males to females, with apparent energetic costs for females.

Genetic and morphological diversity and population structure of a polyploid complex of Mimosa (Leguminosae) - Matías Morales; Florencia Giannoni; María V. Inza; MaríA C. Soldati; Cecilia F. Bessega; Lidia Poggio; Noga Zelener; Renée H. Fortunato (Systematics and Biodiversity, 2020)

Ecosystem services for conservation finance: applying the TEEB stepwise approach in Côte d’Ivoire - Augustin Berghöfer; Joshua Berger; Inza Koné; Ulrike Tröger; Hans Ulrich Caspary (Biodiversity and Conservation, 2018)

Genetic variability of Araucaria angustifolia in the Argentinean Parana Forest and implications for management and conservation - María Virginia Inza; Natalia Cristina Aguirre; Susana Leonor Torales; Norberto Manuel Pahr; Hugo Enrique Fassola; Luis Fernando Fornes; Noga Zelener (Trees, 2018)

Zinc, copper, cadmium, and lead concentrations in water, sediment, and Anadara senilis in a tropical estuary - Inza Bakary; Koffi Marcellin Yao; Olivier Assoi Etchian; Metongo Bernard Soro; Albert Trokourey; Yobou Bokra (Environmental Monitoring and Assessment, 2015)

What is the genetic origin of teak (Tectona grandis L.) introduced in Africa and in Indonesia? - Daniel Verhaegen; Inza Jesus Fofana; Zénor A. Logossa; Daniel Ofori (Tree Genetics & Genomes, 2010)

Diversity and genetic structure of teak (Tectona grandis L.f) in its natural range using DNA microsatellite markers - Inza Jesus Fofana; Daniel Ofori; Mireille Poitel; Daniel Verhaegen (New Forests, 2009)

Presence of Arcobacter spp. in environmental waters correlates with high levels of fecal pollution - Luis Collado; Isabel Inza; Josep Guarro; Maria Jose Figueras (Environmental Microbiology, 2008)
Summary We investigated the presence of Arcobacter spp. in 205 water samples of freshwater, seawater and sewage in Spain. These bacteria were present in 55.1% of the samples (113/205) and were significantly associated for the first time with bacterial indicators of fecal pollution. The dominant species in the positive samples was Arcobacter butzleri (94%) followed by Arcobacter cryaerophilus (30%) and Arcobacter skirrowii (1.8%).

The Southern Region of Peru Earthquake of June 23rd, 2001 - Hernando Tavera; Efraín Fernández; Isabel Bernal; Yanet Antayhua; Consuelo Agüero; Henry Salas Simeón Rodríguez; Luis Vilcapoma; Yolanda Zamudio; David Portugal; Adolfo Inza; Julia Carpio; Freddy Ccallo; et al. (Journal of Seismology, 2006)

Market Hunting in the Taï Region, Côte d’Ivoire and Implications for Monkey Populations - Johannes Refisch; Inza Koné (International Journal of Primatology, 2005)

Prevalence of Salmonella serotypes in environmental waters and their relationships with indicator organisms - F. Polo; M.J. Figueras; I. Inza; J. Sala; J.M. Fleisher; J. Guarro (Antonie van Leeuwenhoek, 1999)